Improving Students’ Writing Skill Using Textless Comic - Alin Fir Handayani; Ayu Istiana Sari (English Education Department Slamet Riyadi University Surakarta, 2023)
Thisystudyyaims to identify whether the use of textless comic improveedthe students’sskill in writing recount texts. The subject of this study were the eight gradedstudents of Public Junior High School in Central Java. The method study was a ClassroomaActionnResearch. Theestudy was conducteddinntwoocycles. Todcollecttthe data, thedresearcherrusedstest such asdpre-test andppost-test. To analyzedthe data, therresearcher used quantitative datadanalysiscby using mean score. The researcher used a formula proposes by Arikunto (2010) to count the meantscore. The resulttof the research show that textlesstcomictmediascan improvesthe students’tskilltinawritingrrecount texts. The improvements of the students’twriting skill were in composing a logical sequence of ideas. Besides, the improvementoofcthe students’wwriting skillrcan be seen from the students’ writing achievement. The result of meantscore formpre-testkwas 56, in post-tests1, it was 72, and inppost-test 2, it was 77. It cannbe concluded that textlessdcomicmmedia can improve the students’dwriting skill especially in determining the logical sequence of stories in writing recount text.Keyword: Writing Skill, Textless Comic Media, Classroom Action Research.